Effect of Transcutaneous Electrical Nerve Stimulation Versus Capsicum Plaster on Emesis Gravidarum - Milad, Peter Bahgat; Hanafy, Hala Mohamed; Awad, Mohamed Ahmed Mohamed; Gabr, Amir Arabi (Journal of Neonatal Surgery, 2025)
Objectives: To determine the difference between the effects of transcutaneous electrical nerve stimulation and capsicum plaster on emesis gravidarum. Design: Randomized clinical trial. Location: This study was conducted at Kasr El Ainy University Hospital, Cairo, Egypt. Subjects: Fifty pregnant women with emesis gravidarum were split into two equal groups. They were between the ages of 20 and 35 years, with gestational age less than 20 weeks. Intervention: Group (A) received transcutaneous electrical nerve stimulation (TENS) at p6 with the following parameters: Frequency: 80–120 Hz, Pulse width: 150 ms, Duration: 15 minutes for 30 consecutive days. Group (B) received capsicum plaster on p6 point for 12 hours per day for 30 consecutive days. Outcome measures: a Rhodes index for nausea, vomiting, and retching. The assessment was performed pre- and post-treatment. Results: Within the group comparison in groups (A) and (B), there was a significant difference in both groups between pre- and post-results. In between-group comparisons, there was no significant change across groups (A) and (B) in decreasing the intensity of distress due to retching, the intensity of distress due to vomiting, the volume of vomiting, or the amount and intensity of distress due to nausea per 24 hours. but there was significance difference between group (A) and (B) in favor of group (B) in decreasing the frequency of vomiting, frequency of retching, frequency and duration of nausea per 24 hours and in the total score of the questionnaire Conclusion: Transcutaneous electrical nerve stimulation and capsicum plaster are both effective in the treatment of emesis gravidarum. Capsicum plaster is more beneficial than transcutaneous electrical nerve stimulation in decreasing the frequency of nausea, retching, and vomiting and reducing the duration of nausea